To punish or to assist? Divergent reactions to ingroup and outgroup members disobeying social distancing - Van Assche, Jasper; Politi, Emanuele; Van Dessel, Pieter; Phalet, Karen (British journal of social psychology, 2020)
In response to the COVID‐19 pandemic, societies face the formidable challenge of developing sustainable forms of sociability‐cumsocial‐distancing – enduring social life while containing the virus and preventing new outbreaks. Accordant public policies often balance between retributive (punishment‐based) and assistance (solidarity‐based) measures to foster responsible behaviour. Yet, the uncontrolled spreading of the disease has divided public opinion about which measures are best suited, and it has made salient group disparities in behaviour, potentially straining intergroup relations, elevating heated emotions, and undercutting coordinated international responses. In a 2 × 2 between‐subjects experiment, British citizens (N = 377) read about national in‐group or outgroup members (categorical differentiation), who were either conforming to or deviating from the corona regulations (normative differentiation). Participants then reported moral emotions towards the target national group and indicated support for public policies. In general, support for assistance policies outweighed support for retributive measures. Second, however, norm deviation was associated with less positive and more negative moral emotions, the latter category further relating to more punitiveness and less assistance support. Finally, respondents who read about norm‐violating outgroup members especially reported support for retributive measures, indicating that people might use norm deviation to justify outgroup derogation. We discuss implications for policymakers and formulate future research avenues.